DIPPING PATTERN AND SHORT-TERM BLOOD PRESSURE VARIABILITY ARE STRONGER PREDICTORS OF CARDIOVASCULAR EVENTS THAN AVERAGE 24-HOUR BLOOD PRESSURE IN HYPERTENSION OF THE YOUNG. (April 2021) - Palatini, Paolo; Reboldi, Paolo; Saladini, Francesca; Angeli, Fabio; Mos, Lucio; Fania, Claudio; Mazzer, Adriano; Vriz, Olga; Verdecchia, Paolo
Abstract : Objective: Ambulatory blood pressure (ABP) monitoring (ABPM) is currently performed for stratification of risk in hypertension. However, in clinical practice interest is focused on average ABP whereas little attention is paid to other ABPM parameters. Previous data have been obtained mainly from populations including elderly individuals, while little is known on the clinical significance of ABPM data in young individuals. Aim of the present study was to investigate whether and to what extent parameters other than average ABP are associated with CVE in individuals <= 45 years of age. Design and method: We performed ABPM in 2356 young-to-middle-age participants enrolled in 2 prospective studies in Italy (HARVEST and PIUMA). Mean age was 35.6 ± 7.6 years and mean BP was 143.3 ± 15.7/93.5 ± 10.6 mmHg. The ABPM parameters of interest were average 24 h systolic BP (SBP), 24 h systolic SD, and 24 h SBP diurnal rhythm. Participants were grouped according to whether they had high or low average 24 h SBP (cutoff, 130 mmHg), high or low systolic SD (cutoff, 12.8 mmHg), and were dippers or nondippers (cutoff 10% nocturnal decline). All parameters were included simultaneously in the same Cox models. Hazard ratios (HR) were adjusted for traditional risk factors. Results: During a median follow-up of 12.4 years, 164 CVE were observed. All ABPM parameters were independent predictors of the endpoints. However, a higher risk was observed for non dipping (HR, 2.4; 95%CI, 1.6–3.6; p < 0.0001) and for high SD (HR, 2.0; 1.4–2.8; p = 0.0002) than for high average SBP (HR, 1.5; 1.1–2.2; p = 0.019). Compared to dippers with low average SBP, nondippers with high average SBP had a HR of 3.2 (95%CI, 2.2–5.2). Compared to participants with low SD and low average SBP, participants with high average SBP and high SD had a HR of 2.8 (2.7–4.6). Similar results were obtained in the 1780 hypertensives and when the ABPM parameters were used as continuous variables. Conclusions: In young-to-middle-age subjects, dipping pattern and short-term BP variability are strong predictors of adverse outcome on top of average 24-hour BP. These two parameters should always be included in the stratification of risk when young hypertensive patients are assessed with ABPM.